Impact of public policies regarding employment in Colombia during the year 2020 in a stage by COVID-19 (2021)
The global health emergency forced countries to take measures, this brought great social and economic problems. Colombia took measures to counteract the spread of the virus, however, the confinement had effects on labor matters in the country. This Essay aims to analyze the impact of public policies on employment in 2020 in a COVID-19 scenario, the type of study used is documentary, using the analytical method. From this, a high percentage of the unemployment rate was evidenced in the course of 2020. It was possible to conclude that the repercussions of the public policies implemented were positive because they contributed to mitigating the increase in unemployment, as well as promoting the employment during the crisis.